Enhancing Capacity for Local Economic Development in Creating Vibrant, Productive and Sustainable Rural Communities - Parker, Gail, Denise; Costa, King (My University, 2021)
Since the advent of South Africa’s democracy, there have been many pressing questions; one of which has been: ‘to what extent has the newly found political and civil freedoms, which is guaranteed for all South Africans, translated into an a more economically-viable life?’ This research investigated whether local economic development (LED) interventions necessarily improve the livelihoods of poor communities. The methods used were hinged upon the interpretivist paradigm, using literature as a basis of enquiry. Furthermore, semi-structured interviews with target groups (eg. project beneficiaries, government officials, municipal manager, town mayor, etc) were conducted, followed by focus group-style interviews with key stakeholders. The study found that sound economic development vision may thrive if linked to the following: clear policy guidance, institutional capacity building, intersectoral collaboration, political will and real empowerment.
Keywords: Economic activity; Empowerment initiative; Intersectoral collaboration; Local economic development; Policy guidance